Proposing A Web-Based Interactive Module for Education for Sustainable Development In English for Computer Science - Dewi Sari Wahyuni; Yenni Rozimela; Havid Ardi; Mukhaiyar Mukhaiyar; T. Sy. Eiva Fatdha (IAIN Salatiga, 2023)
English for Computer Science (ECS), as part of English for Specific Purposes (ESP), is designed to teach students the English required in computer science. In this paper, the writers proposed to incorporate Education for Sustainable Development (ESD) into ECS to encourage student engagement by presenting current concerns relevant to their life experiences. The work is a position paper in which the writers argue for the importance of building a web-based interactive module for ESD in ECS. Our arguments are supported in the following sections; English for Specific Purposes (ESP), Content Language Integrated Learning (CLIL), English for Computer Science (ECS), Education for Sustainable Development (ESD), Instructional Material limited to Module and E-Module, and related research. The writers propose developing an interactive web-based module for ESD in ECS so that students have more fun while they are studying. It is anticipated that students will be able to study the module at their own pace and according to their capabilities. This module is paperless; it contributes to the Sustainable Development Goals (SDGs). As instructional materials, the module will also assist ECS students in overcoming classroom time constraints and relating what they learn to future concerns, careers, and professionalism.Keywords: web-based interactive module; education for sustainable development; english for computer science